Accelerated partial breast irradiation using intensity-modulated radiotherapy versus whole breast irradiation: 5-year survival analysis of a phase 3 randomised controlled trial. Issue 4 (March 2015) - Livi, Lorenzo; Meattini, Icro; Marrazzo, Livia; Simontacchi, Gabriele; Pallotta, Stefania; Saieva, Calogero; Paiar, Fabiola; Scotti, Vieri; De Luca Cardillo, Carla; Bastiani, Paolo; Orzalesi, Lorenzo; Casella, Donato; et al.
Abstract Background Accelerated partial breast irradiation (APBI) has been introduced as an alternative treatment method for selected patients with early stage breast cancer (BC). Intensity-modulated radiotherapy (IMRT) has the theoretical advantage of a further increase in dose conformity compared with three-dimensional techniques, with more normal tissue sparing. The aim of this randomised trial is to compare the local recurrence and survival of APBI using the IMRT technique after breast-conserving surgery to conventional whole-breast irradiation (WBI) in early stage BC. Methods This study was performed at the University of Florence (Florence, Italy). Women aged more than 40 years affected by early BC, with a maximum pathological tumour size of 25 mm, were randomly assigned in a 1:1 ratio to receive either WBI or APBI using IMRT. Patients in the APBI arm received a total dose of 30 Gy to the tumour bed in five daily fractions. The WBI arm received 50 Gy in 25 fractions, followed by a boost on the tumour bed of 10 Gy in five fractions. The primary end-point was occurrence of ipsilateral breast tumour recurrences (IBTRs); the main analysis was by intention-to-treat. This trial is registered with ClinicalTrials.gov, number NCT02104895. Findings A total of 520 patients were randomised (260 to external WBI and 260 to APBI with IMRT) between March 2005 and June 2013. At a median follow-up of 5.0 years (Interquartile Range (IQR) 3.4–7.0), the IBTR rate was 1.5% (three cases) in the APBI group (95% confidence interval (CI) 0.1–3.0) and in the WBI group (three cases; 95% CI 0.0–2.8). No significant difference emerged between the two groups (log rank test p = 0.86). We identified seven deaths in the WBI group and only one in the APBI group (p = 0.057). The 5-year overall survival was 96.6% for the WBI group and 99.4% for the APBI group. The APBI group presented significantly better results considering acute (p = 0.0001), late (p = 0.004), and cosmetic outcome (p = 0.045). Interpretation To our knowledge, this is the first randomised study using the IMRT technique for APBI delivery. No significant difference in terms of IBTR and overall survival was observed between the two arms. APBI displayed a significantly better toxicity profile.